The Optimal Formula for Organic Oil Immobilization in Algerian Petroleum Drill Cuttings Using Solidification/Stabilisation Treatment - Abbas, Abbas Hadj; Sagala, Farad; Hacini, Messaoud (Research Square, 2021)
Hassi Messaoud oil field is one of the most important fields in Algeria and the world, because it covers an important quantity of total Crude Oil Production in Algeria. Furthermore, two-thirds of this oil field is underexplored or not explored. Therefore, the drilling process of petroleum wells in this field is a continuous process that results in significant drilling waste. This implies that, enormous noxious quantities of drilling waste are produced daily that require treatment via solidification/stabilization (S/S) process before being landfilled. These types of wastes have pollution concentration that significantly exceeds the safety standards. In this study, we focus on the factors affecting the solidification/stabilization treatment of the drill cuttings obtained from Hassi Messaoud oil field and the process optimization. The solidification/stabilization is performed using the cement as binder, sand, silicate, organophilic clay and activated carbon as additives.
Keywords: drill cuttings, solidification/stabilization, Portland cement, compressive strength, Total Petroleum Hydrocarbon